Rod-shaped cerium oxide loaded metal catalyst and method for preparing cis-pinane by using catalyst
By using rod-shaped cerium oxide-supported nickel and ruthenium metal catalysts, the α-pinene hydrogenation reaction is carried out at near room temperature and low hydrogen pressure, the problems of harsh reaction conditions and easy catalyst deactivation in the prior art are solved, and efficient and stable cispinene generation is achieved.
Patent Information
- Application Number
- CN202510292013.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-06-13
AI Technical Summary
The prior art has harsh reaction conditions in the α-pinene hydrogenation reaction, the catalyst is prone to coking, has poor reusability, and is dangerous to operate, making it difficult to efficiently generate cispinene under mild conditions.
A rod-shaped cerium oxide-supported metal catalyst is used. The microstructure of the catalyst is nanorod-shaped, and the metal-support interaction is strong to avoid agglomeration. The supported metals are nickel and ruthenium, with a loading amount of 1 to 20%. The hydrogenation reaction is carried out at near room temperature and low hydrogen pressure conditions.
The hydrogenation reaction of α-pinene is efficiently realized under near room temperature and low hydrogen pressure. The conversion rate of α-pinene is >99%, the selectivity of cis-pinene is >98%, the catalyst is resistant to carbon deposits, and has strong cycle stability, which is suitable for industrial production.
Smart Images

Figure CN120132843A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of chemical engineering, and particularly relates to a metal catalyst supported on rod-shaped cerium oxide and a method for preparing cis-pinane using the catalyst. Background Art
[0002] α-Pinene is the main component of turpentine, a biomass resource. Its hydrogenation reaction can produce pinane. Pinane is the main raw material for synthesizing terpene fragrances and pharmaceutical intermediates such as dihydromyrcene, linalool, citronellol, and citronellal. The hydrogenation of α-pinene usually produces two isomeric products - cis-pinane and trans-pinane. Cis-pinane exhibits higher reactivity in the synthesis of downstream products and has fewer side reactions. Therefore, it is the more favored target product during the hydrogenation of α-pinene. The traditional industrial process for the hydrogenation of α-pinene mainly uses a Raney-Ni catalyst, which is carried out under high temperature and high pressure (100 - 160 °C, 2.0 - 2.5 MPa H 2 )). The reaction conditions are harsh, the catalyst is prone to coking, its reusability is poor, and Raney-Ni is flammable, making the production operation very dangerous. Therefore, developing a new process to efficiently produce cis-pinane from α-pinene under mild conditions has important practical significance.
[0003] So far, researchers have developed a series of process catalysts for the hydrogenation of α-pinene to prepare cis-pinane, mainly including various noble metal and non-noble metal catalysts. Patent CN1262263A reports a transition metal-modified Ni-Al alloy catalyst, which reacts at 70 - 110 °C and 2.0 - 3.0 MPa for 3 - 6 h, with an α-pinene conversion rate ≥ 99% and a cis-pinane selectivity ≥ 96%. Patent CN113735677B introduces a method for catalyzing the hydrogenation of α-pinene to prepare cis-pinane using a ruthenium catalyst supported on L-malic acid intercalated magnesium-aluminum hydrotalcite (Ru / Mg-Al-L-(-)-MA LDH). This method is carried out under the conditions of a temperature of 100 - 140 °C and a hydrogen pressure of 2 - 4 MPa, with an α-pinene conversion rate > 96% and a cis-pinane selectivity ≥ 95%. Patent CN107519867A reports a catalyst using ruthenium supported on titanium dioxide (Ru / TiO 2)A method for the selective hydrogenation of α-pinene to synthesize cis-pinane, with reaction conditions of temperature 100 - 140 °C, hydrogen pressure 2 - 5 MPa, reaction time 3 - 7 h, α-pinene conversion rate > 96%, and cis-pinane selectivity > 95%. Although these reported methods all show high α-pinene conversion rates and cis-pinane selectivities, the reaction conditions are harsh, with high hydrogenation reaction temperature and pressure, high operating costs, and it is easy to cause coking and deactivation of the catalyst. Patent CN105418355A reports the use of PVA-stabilized nano-ruthenium micelles, and the α-pinene conversion rate can reach 99.6% under the conditions of 50 - 80 °C, hydrogen pressure 1 - 4 MPa, and reaction time 1 - 3 h, with cis-pinane selectivity > 99.1%; Patent CN104844408B adopts a similar stabilizer strategy, using P123-stabilized nano-ruthenium micelles to react at 40 °C and 0.7 MPa for 2 h, with α-pinene conversion rate > 95% and cis-pinane selectivity > 98%. Although the above two nano-ruthenium micelle systems have achieved the hydrogenation reaction of α-pinene under relatively mild conditions, this type of ligand-stabilized metal nano-catalyst has serious defects and is prone to the problem of ligand loss, resulting in rapid deactivation of the catalyst. At present, developing a stable and efficient catalyst for the hydrogenation of α-pinene to cis-pinane under mild conditions is still a difficult challenge. Summary of the Invention
[0004] The object of the present invention is to provide a new process for the efficient hydrogenation of α-pinene to prepare cis-pinane using a supported metal catalyst under near-room temperature conditions. This process has beneficial effects such as mild reaction conditions, high product yield, good reaction activity, and strong catalyst cycle stability.
[0005] To achieve the above object, a metal catalyst supported on rod-shaped cerium oxide of the present invention has a nanorod-shaped microstructure. The ratio of the length to the width (or diameter) of the nanorods is 2 - 60, with developed stacked voids, strong metal-support interaction and anti-agglomeration; the carrier of the catalyst is rod-shaped cerium oxide with rich oxygen vacancy defects on the surface, and the metal nanoparticles are evenly dispersed on the surface of the carrier, with an average particle size less than 10 nm; the supported metal is one or two of nickel and ruthenium; in the composition of the catalyst, the mass fraction of the supported metal is 1 - 20%; when loading two metals, the molar ratio of nickel to ruthenium is 0.05 - 20.
[0006] A method for preparing cis-pinane using a rod-shaped cerium oxide-supported metal catalyst. The cerium oxide-supported metal catalyst and α-pinene are placed in a reaction kettle, and the gas inside the reaction kettle is replaced with hydrogen or a hydrogen mixed gas. Then, the pressure inside the reaction kettle is controlled at 0.1 - 2.0 MPa, the temperature inside the reaction kettle is 15 - 60 °C, the stirring speed is 500 - 1200 r / min, the reaction time is 0.5 - 5 h, and then it is cooled naturally to obtain cis-pinane.
[0007] Preferably, the dosage of the supported metal catalyst is 0.5 - 15% of the weight of α-pinene.
[0008] Preferably, the α-pinene can be in a solvent-free form or in the form of a solution dissolved in an organic solvent; the organic solvent is any one of methanol, ethanol, ethylene glycol, 1-propanol, 2-propanol, 1,2-propanediol, 1,3-propanediol, and 1-butanol.
[0009] Preferably, the pressure range inside the reaction kettle is 0.2 - 1.0 MPa; the hydrogen mixed gas is a mixture of hydrogen and an inert gas, and the inert gas is at least one of nitrogen, argon, and helium. The number of replacement times is 3 - 7 times.
[0010] Preferably, the temperature inside the reaction kettle is 25 - 40 °C.
[0011] A method for preparing a rod-shaped cerium oxide-supported metal catalyst includes the following steps:
[0012] Step (1): Mix a cerium salt solution with an alkaline solution and react under stirring conditions to form a precursor precipitate; transfer the obtained mixture to a hydrothermal reaction kettle and perform hydrothermal treatment at a temperature of 80 - 200 °C. After the reaction is completed, wash the obtained solid product to neutrality and dry it, and calcine the dried sample in an air atmosphere. The calcination temperature is 300 - 1000 °C to obtain a cerium oxide support.
[0013] Step (2): Immerse the obtained cerium oxide support in a salt solution of an active metal and stir at room temperature for 0.5 - 12 h. Perform high-temperature reduction of the dried sample in a hydrogen atmosphere. The high-temperature reduction temperature is 300 - 800 °C, and the reduction time is 0.5 - 10 h. Let the reduced sample cool naturally to obtain a cerium oxide-supported metal catalyst.
[0014] Preferably, in step (1), the cerium salt is cerium nitrate, cerium chloride, and cerium sulfate, and the alkaline solution is sodium hydroxide, potassium hydroxide, and ammonia water. The stoichiometric ratio of the added cerium salt to the base is 0.005 - 10.
[0015] Preferably, in the step (1), the heat treatment time of the water is 2 to 72 h, the drying temperature is 25 to 60 °C, the drying time is 2 to 24 h, and the calcination time is 1 to 10 h.
[0016] Preferably, in the step (2), the mass ratio of the cerium oxide support to the salt solution of the active metal is 4 to 99.
[0017] Preferably, in the step (2), the salt solution of the active metal is at least one of nickel salt and ruthenium salt, the nickel salt is nickel nitrate, nickel chloride, nickel sulfate, nickel acetate; the ruthenium salt is ruthenium nitrate, ruthenium chloride, ruthenium sulfate, ruthenium acetate.
[0018] The technical effect of the present invention is that the metal catalyst supported on rod-shaped cerium oxide and the α-pinene hydrogenation process are used to prepare cis-pinane, which can be efficiently realized under near room temperature and very low hydrogen pressure conditions. The α-pinene conversion rate > 99%, the cis-pinane selectivity > 98%, the catalyst resists carbon deposition, can be reused multiple times without deactivation, avoids frequent replacement of new catalysts, has higher production efficiency, and is simple and safe to operate, suitable for industrial production. Description of the Drawings
[0019] Figure 1 (a) and 1(c) are transmission electron microscope images of a ruthenium metal catalyst supported on cerium oxide prepared by the method of the present invention at different scales;
[0020] Figure 1 (b) is the particle size statistical distribution diagram of the nano-ruthenium particles on the catalyst surface;
[0021] Figure 1 (d) is the electron paramagnetic resonance (EPR) spectrum of the catalyst.
[0022] Figure 2 It is a graph showing the change trend of the performance of the catalyst in the cyclic stability test. Detailed Description of the Invention
[0023] The following Examples 1-16 will be used to illustrate in detail the beneficial effects of the present invention, aiming to help readers better understand the essence of the present invention, but cannot limit the implementation and protection scope of the present invention.
[0024] Example 1:
[0025] 50 mL of an aqueous solution containing 14.4 g of NaOH was gradually added to 10 mL of a solution containing 1.3 g of Ce(NO 3 ) 3 ·6H 2In an aqueous solution of O, after stirring for 1 h, the mixed solution was transferred to a 100 mL hydrothermal reactor and reacted at a constant temperature of 100 °C for 24 h. After the reaction was completed, the obtained precipitate was washed with deionized water until neutral. Subsequently, it was dried in vacuo at 60 °C for 12 h and calcined in a muffle furnace at 400 °C in an air atmosphere for 4 h to finally obtain a cerium oxide support, denoted as CeO 2 -400 (where 400 represents the muffle furnace calcination temperature).
[0026] 8.76 g of Ni(NO 3 ) 2 ·6H 2 O was dissolved in 30 mL of deionized water. 10 g of CeO 2 -400 powder was added to the nickel salt solution for uniform impregnation. After stirring for 2 h, the solvent was removed by rotary evaporation and drying. It was reduced at 600 °C for 6 h in a hydrogen atmosphere to obtain catalyst 1 (Ni / CeO 2 -400), and the loaded mass fraction of Ni was 15%.
[0027] In the reaction kettle, 10 g of α-pinene and 0.1 g of catalyst Ni / CeO 2 -400 were added in sequence. After replacing the air in the kettle with hydrogen 5 times, 0.5 MPa of hydrogen was charged. The mixture was stirred and heated to 40 °C at a stirring speed of 600 r / min. After maintaining the constant temperature reaction for 2 h, it was allowed to stand and cool to room temperature. Gas chromatography was used for analysis to calculate the conversion rate of α-pinene and the selectivity of cis-pinane.
[0028] Example 2:
[0029] The catalyst used in this example was the same as that in Example 1 (Ni / CeO 2 -400). The difference was that the reaction temperature during the hydrogenation reaction was lowered to 30 °C, and other reaction conditions were the same as those in Example 1.
[0030] Example 3:
[0031] The catalyst used in this example was the same as that in Example 1 (Ni / CeO 2 -400). The difference was that the reaction temperature during the hydrogenation reaction was lowered to 25 °C, and other reaction conditions were the same as those in Example 1.
[0032] Example 4:
[0033] The catalyst used in this example was the same as that in Example 2 (Ni / ZnO). The difference was that the reaction pressure during the hydrogenation reaction was lowered to 0.3 MPa, and other reaction conditions were the same as those in Example 1.
[0034] Example 5:
[0035] The catalyst preparation process was the same as that of Example 1, except that the calcination temperature in the muffle furnace was increased to 600 °C to obtain Catalyst 5 (Ni / CeO 2 -600), and the mass fraction of Ni loading was 15%. The hydrogenation reaction process was the same as that in Example 4.
[0036] Example 6:
[0037] The catalyst preparation process was the same as that of Example 1, except that the calcination temperature in the muffle furnace was increased to 800 °C to obtain Catalyst 5 (Ni / CeO 2 -800), and the mass fraction of Ni loading was 15%. The hydrogenation reaction process was the same as that in Example 4.
[0038] Example 7:
[0039] Dissolve 1.16 g of RuCl 3 ·3H 2 O in 50 mL of absolute ethanol, add 10 g of CeO 2 -400 powder in the example to the ruthenium salt solution for uniform impregnation. After stirring for 2 h, rotate and evaporate to remove the solvent, and reduce it at 500 °C for 6 h in a hydrogen atmosphere to obtain Catalyst 7 (Ru / CeO 2 -400), and the mass fraction of Ru loading was 3%. In the autoclave, add 10 g of α-pinene and 0.1 g of catalyst Ru / CeO 2 -400 in sequence. Replace the air in the autoclave with hydrogen 5 times and then fill it with 0.5 MPa of hydrogen. Stir and heat up to 30 °C, with a stirring speed of 600 r / min. React at a constant temperature for 2 h, let it stand and cool to room temperature, and analyze by gas chromatography to calculate the conversion rate of α-pinene and the selectivity of cis-pinane.
[0040] Example 8:
[0041] The catalyst preparation process was the same as that of Example 7, except that the amount of RuCl 3 ·3H 2 O was 2.4 g to obtain Catalyst 7 (Ru / CeO 2 -400), and the mass fraction of Ru loading was 6%. The hydrogenation reaction process was the same as that in Example 6.
[0042] Example 9:
[0043] The used Catalyst 9 was the same as the catalyst (Ru / CeO 2 -400) used in Example 8. The hydrogenation reaction process was the same as that in Example 8, except that the reaction temperature in the hydrogenation reaction process was reduced to 25 °C, and other reaction conditions were the same as those in Example 8.
[0044] Example 10:
[0045] The preparation process of the catalyst was the same as that in Example 7, except that 10 g of CeO 2 -400 powder was replaced with 10 g of CeO 2 -600 powder to obtain catalyst 10 (Ru / CeO 2 -600), and the loading mass fraction of Ru was 3%. The hydrogenation reaction process was the same as that in Example 7.
[0046] Example 11:
[0047] Dissolve 0.980 g of RuCl 3 ·3H 2 O and 0.819 g of Ni(NO 3 ) 2 ·6H 2 O in 50 mL of an ethanol aqueous solution (ethanol mass fraction 50%). Add 10 g of CeO 2 -400 powder to the above mixed solution of ruthenium salt and nickel salt for uniform impregnation. After stirring for 2 h, rotate and evaporate to remove the solvent. Reduce it at 500 °C for 6 h under a hydrogen atmosphere to obtain catalyst 11 (NiRu / CeO 2 -400), with a metal loading of 6 wt% and a molar ratio of Ni / Ru = 1 / 1. In the reaction kettle, add 10 g of α-pinene and 0.1 g of catalyst NiRu / MgO in sequence. Replace the air in the kettle with hydrogen 5 times and then fill it with 0.5 MPa of hydrogen. Stir and heat up to 30 °C, with a stirring speed of 600 r / min. React at a constant temperature for 2 h, let it stand and cool to room temperature, and analyze by gas chromatography to calculate the conversion rate of α-pinene and the selectivity of cis-pinane.
[0048] Example 12:
[0049] The catalyst preparation process was the same as that in Example 11, except that the CeO 2 -400 powder was replaced with CeO 2 -600 powder to obtain catalyst 12 (NiRu / CeO 2 -600), with a metal loading of 6 wt% and a molar ratio of Ni / Ru = 1 / 1. The hydrogenation reaction process was the same as that in Example 11.
[0050] Example 13:
[0051] The catalyst preparation process was the same as that in Example 11, except that the addition amount of RuCl 3 ·3H 2 O was 0.516 g, and the addition amount of Ni(NO 3 ) 2 ·6H 2 O was 1.490 g to obtain catalyst 13 (NiRu / CeO 2-600), metal loading of 6 wt%, molar ratio of Ni / Ru = 2 / 1. The hydrogenation reaction process was the same as in Example 12.
[0052] Example 14:
[0053] The catalyst preparation process was the same as in Example 1, except that the hydrothermal reaction temperature of the autoclave was increased to 160 °C to obtain catalyst 14 (Ni / CeO 2 -400-160), metal loading of 15 wt%. The hydrogenation reaction process was the same as in Example 1.
[0054] Comparative Example 15:
[0055] In the reaction kettle, 10 g of α-pinene and 0.1 g of commercial Raney-Ni catalyst were added in sequence. After replacing the air in the kettle with hydrogen 5 times, 0.5 MPa of hydrogen was charged. The mixture was stirred and heated to the reaction temperature of 30 °C, and reacted at a constant temperature for 2 h. Then it was allowed to stand and cool to room temperature, and analyzed by gas chromatography to calculate the conversion rate of α-pinene and the selectivity of cis-pinane.
[0056] Comparative Example 16:
[0057] In the reaction kettle, 10 g of α-pinene and 0.1 g of commercial Pd / C catalyst (Pd mass fraction 5%) were added in sequence. After replacing the air in the kettle with hydrogen 5 times, 0.5 MPa of hydrogen was charged. The mixture was stirred and heated to the reaction temperature of 30 °C, and reacted at a constant temperature for 2 h. Then it was allowed to stand and cool to room temperature, and analyzed by gas chromatography to calculate the conversion rate of α-pinene and the selectivity of cis-pinane.
[0058] The temperatures, hydrogen pressures, catalysts used, and final α-pinene conversion rates and cis-pinane selectivities of the reaction processes in Examples 1-14 and Comparative Examples 15-16 above are listed in Table 1 to more intuitively reflect the excellent performance obtained by using the process of this patent.
[0059] Table 1 Catalytic performance of catalysts in Examples and Comparative Examples
[0060]
[0061] Figure 1 (a) and 1(c) are transmission electron microscope images of a ruthenium metal catalyst supported on cerium oxide prepared by the method described in the present invention at different scales; Figure 1 (b) is the particle size statistical distribution diagram of the nano ruthenium particles on the catalyst surface; Figure 1 (d) is the electron paramagnetic resonance (EPR) spectrum of the catalyst. It can be seen from the transmission electron microscope images that the microstructure of the catalyst is in the form of interlaced stacked nanorods, and this interlaced morphology can form developed voids, which is beneficial to the rapid diffusion of the reactant α-pinene and the product pinane, and this promotes the acceleration of the reaction rate.Figure 1 (b) shows that the average particle size of ruthenium nanoparticles on the catalyst surface is only 4.0 nm, indicating that ruthenium metal is highly dispersed on the support surface, which can expose more metal active sites and improve the catalytic reaction rate of α-pinene hydrogenation. Figure 1 (d) shows that the catalyst surface has abundant oxygen vacancy defects, which is beneficial to the dispersion of ruthenium metal. At the same time, oxygen defects can strengthen the interaction between the support and the metal. In this way, metal nanoparticles are not prone to agglomeration during the catalytic α-pinene hydrogenation reaction, and the rapid deactivation of the catalyst can be slowed down or avoided.
[0062] Figure 2 It is a graph showing the change trend of the catalytic performance of the catalyst in the cyclic stability test. It can be seen from it that during the 30 cycles of the catalyst, the conversion rate of α-pinene and the selectivity of cis-pinane basically do not decrease significantly, indicating that the catalyst has very excellent cyclic stability.
[0063] The above figures only help to understand the connotation of the present invention through the characterization of a typical sample, and do not limit the scope of the claims of the present invention. Any changes in the microstructure of the catalyst by those skilled in the art through conventional technical means (such as the bonding of nanorods into slightly massive blocks or slight changes in the EPR signal intensity of oxygen vacancies, etc.) should fall within the scope of the claims of the present invention.
[0064] The embodiments described above are only used to describe the preferred embodiments of the present invention, and do not limit the scope of the present invention. Without departing from the design spirit of the present invention, various deformations and improvements made by those of ordinary skill in the art to the technical solutions of the present invention should be included in the protection scope determined by the claims of the present invention.
Claims
1. A rod-shaped cerium oxide-supported metal catalyst, characterized in that: The microstructure of the catalyst is in the shape of nanorods, the ratio of the length to the width of the nanorods is 2-60, and the catalyst has developed stacking gaps and strong anti-agglomeration of the metal-carrier interaction; the catalyst carrier is rod-shaped cerium oxide with abundant oxygen vacancy defects on the surface, and the metal nanoparticles are evenly dispersed on the carrier surface with an average particle size of less than 10 nm; the loaded metal is one or two of nickel and ruthenium; in the catalyst composition, the mass fraction of the loaded metal is 1-20%; when the two metals are loaded, the molar ratio of nickel to ruthenium is 0.05-20.
2. The method for preparing cis-pinane using a rod-shaped cerium oxide-supported metal catalyst according to claim 1, characterized in that: The cerium oxide-loaded metal catalyst and α-pinene are placed in a reactor, the gas inside the reactor is replaced with hydrogen or a hydrogen mixed gas, and then the internal pressure of the reactor is controlled at 0.1-2.0 MPa, the temperature in the reactor is 15-60° C., the stirring speed is 500-1200 r / min, the reaction time is 0.5-5 h, and then the temperature is naturally lowered to obtain cis-pinene.
3. The method according to claim 2, characterized in that The amount of the supported metal catalyst used is 0.5-15% of the weight of α-pinene.
4. The method according to claim 2, characterized in that: The α-pinene may be in a solvent-free form or in a solution form dissolved in an organic solvent; the organic solvent is any one of methanol, ethanol, ethylene glycol, 1-propanol, 2-propanol, 1,2-propylene glycol, 1,3-propylene glycol and 1-butanol.
5. The method according to claim 2, characterized in that: The pressure in the reactor ranges from 0.2 to 1.0 MPa; the hydrogen mixed gas is a mixture of hydrogen and an inert gas, and the inert gas is at least one of nitrogen, argon, and helium.
6. The method according to claim 2, characterized in that The temperature in the reactor is 25-40°C.
7. A method for preparing a rod-shaped cerium oxide-supported metal catalyst according to claim 1, characterized in that: The following steps are involved: Step (1): mixing a cerium salt solution with an alkaline solution, and reacting them under stirring conditions to form a precursor precipitate; The obtained mixture is transferred to a hydrothermal reactor and subjected to hydrothermal treatment at a temperature of 80-200° C. After the reaction is completed, the obtained solid product is washed to neutrality and dried, and the dried sample is calcined in an air atmosphere at a calcination temperature of 300-1000° C. to obtain a cerium oxide carrier; Step (2): immersing the obtained cerium oxide support in a salt solution of an active metal, stirring at room temperature for 0.5 to 12 h, and subjecting the dried sample to high-temperature reduction in a hydrogen atmosphere at a temperature of 300 to 800 °C for a reduction time of 0.5 to 10 h. The reduced sample is naturally cooled to obtain a cerium oxide-supported metal catalyst.
8. The method according to claim 7, characterized in that In the step (1), the cerium salt is cerium nitrate, cerium chloride and cerium sulfate, the alkaline solution is sodium hydroxide, potassium hydroxide and ammonia water, and the stoichiometric ratio of the added cerium salt and the alkali is 0.005-10.
9. The method according to claim 7, characterized in that: In the step (2), the mass ratio of the cerium oxide carrier to the salt solution of the active metal is 4-99.
10. The method according to claim 7, characterized in that The salt solution of the active metal in step (2) is at least one of a nickel salt and a ruthenium salt, wherein the nickel salt is nickel nitrate, nickel chloride, nickel sulfate, or nickel acetate; and the ruthenium salt is ruthenium nitrate, ruthenium chloride, ruthenium sulfate, or ruthenium acetate.
Citation Information
Patent Citations
A kind of method that catalytic α-pinene hydrogenation prepares cis-pinane
CN104844408B
Method for preparing cis-pinane by catalyzing alpha-pinene hydrogenation in aqueous medium
CN105418355A
Preparation method of ruthenium-supported titania catalyst for synthesizing cis-pinane by selective hydrogenation of alpha-pinene
CN107519867A
A method for preparing cis-pinene by hydrogenation of α-pinene catalyzed by L-malic acid intercalated magnesium aluminum hydrotalcite supported ruthenium catalyst
CN113735677B
Improved process for preparing cis-pinane by catalytic hydrogenation of pinene
CN1262263A